Acoustophoretic particle manipulation in hybrid solid/gel resonators - Luzuriaga, Jon; Carreras, Pilar; Candil, Manuel; Bazou, Despina; González, Itziar (Frontiers in Physics, 2022)
This work presents a proof of concept to demonstrate the ability of ultrasounds to perform acoustophoretic processes in hybrid millifluidic resonators that include channels laterally embedded in extremely soft media with physical properties close to those of liquids. In our experiments, particles are driven by acoustic radiation forces towards hydrodynamic/acoustic equilibrium positions in a similar way to that produced in conventional microfluidic resonators with solid structures. 20um-sized polystyrene beads immersed in deionized water flow channelized throughout an aqueous-based gel between an inlet and outlet in a resonant chamber while exposed to ultrasounds at a frequency of 1.54MHz. The liquid channel formed presents irregular walls and variable geometry defined by the sample injection pressure. The particles collect rapidly along a central line equidistant from the walls, regardless of whether they are parallel or not, as observed for different channel geometries and cross section dimensions. Only when the flow stops the particles collect in the acoustic pressure nodes established with 2D spatial distribution. These results break the paradigm of solid structures as essential physical elements to support acoustophoresis, demonstrating for the first time the ability to produce these processes in media without consolidated structure. It opens a door to bioprinting applications.